2017
DOI: 10.21278/brod69109
|View full text |Cite
|
Sign up to set email alerts
|

Probing Into the Effects of Cavitation on Hydrodynamic Characteristics of Surface Piercing Propellers Through Numerical Modeling of Oblique Water Entry of a Thin Wedge

Abstract: SummaryThe current paper investigates flow around a blade section of a surface piercing hydrofoil. To this end, a thin wedge section is numerically modelled through an oblique water entry. The flow is numerically studied using a multiphase approach. The proposed numerical approach is validated in two steps. First, pressure and free surface around a wedge entering water are simulated and compared against previously published analytical results. Subsequently, cavitation phenomenon around a submerged supercavitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The ventilation during water entry had been analysed. Javanmardi, Ghadimi and Tavakoli [23] studied the water entry of a propeller blade impacting on the water surface, the cavitation and ventilation effects on the hydrodynamic characteristic were investigated through Finite volume method. Except the separation-ventilation during the wedge water entry, vortex shedding would develop on the leeward side of the wedge apex in the case of attached flow impact.…”
Section: Introductionmentioning
confidence: 99%
“…The ventilation during water entry had been analysed. Javanmardi, Ghadimi and Tavakoli [23] studied the water entry of a propeller blade impacting on the water surface, the cavitation and ventilation effects on the hydrodynamic characteristic were investigated through Finite volume method. Except the separation-ventilation during the wedge water entry, vortex shedding would develop on the leeward side of the wedge apex in the case of attached flow impact.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Wang 14 extended this method to solve a fully ventilated finite foil shape. Implementation of an analytical method by Ghadimi et al, 15,16 the solution of URANS equation by Javanmardi et al, 17 Ghadimi and Javanmardi, 18 and Ghadimi et al, 19,20 as well as smoothed particle hydrodynamics (SPH) simulations by Farsi and Ghadimi [21][22][23] in studying the water entry of the objects have suggested that the numerical simulation of the viscous flow may be the appropriate choice for modeling the hydrodynamic behavior of the surface-piercing objects. Using two-way coupled URANS and elasticity equations, Javanmardi and Ghadimi 24 showed that the flexibility of the wedge material could affect the ventilation pattern at constant cavitation number and flow angle of attack.…”
Section: Introductionmentioning
confidence: 99%
“…Most of previous investigations concern on the traditional ship and offshore structures such as flat plate [19], stiffened panel [20][21], V-type wedges [22][23][24], spherical ball [25][26], cylindrical projectile [26] and propeller blade wedge section [27] et al In these studies, the common perspective of water entry phenomenon is a typical FSI problem. Obviously, the elasticity of the structures is expected to influence the results of this problem (here, which calls "hydroelasticity").…”
mentioning
confidence: 99%